2009
DOI: 10.1177/0892705709340962
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Particle Size and Coupling Agent Concentration on Mechanical Properties of Particulate-filled Polymer Composites

Abstract: In this study the influence of filler particle size (40, 50, and 60 meshes) and coupling agent concentration (0 and 2 wt%) on the composite mechanical properties were studied. Specimens having 30 wt% wood flour of poplar were mixed with polypropylene and polypropylene grafted maleic anhydride (PP-g-MA) as coupling agent. It was found that strength properties of the composites can be improved moderately by adding 2 wt% PP-g-MA. It was also observed that smaller filler particles provide higher tensile modulus th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 16 publications
9
70
0
3
Order By: Relevance
“…As can be seen, the tensile modulus is not significantly affected by particle size in the range studied; similar results have been reported by Nourbakhsh et al [25], but the tensile strength is affected by particle size. For larger particle size, there is a moderate increase in strength.…”
Section: Tensile Propertiessupporting
confidence: 90%
See 1 more Smart Citation
“…As can be seen, the tensile modulus is not significantly affected by particle size in the range studied; similar results have been reported by Nourbakhsh et al [25], but the tensile strength is affected by particle size. For larger particle size, there is a moderate increase in strength.…”
Section: Tensile Propertiessupporting
confidence: 90%
“…In contrast, Chen et al [24] investigated the effect of wood particle size on wood= HDPE composites and found that plastic composites made of larger wood particles had higher strength. Nourbakhsh et al [25] discussed the effect of wood particle size on wood-flour=PP composites and found that the tensile modulus was not significantly affected by particle size, the tensile strength increased, and the notched izod decreased with decreasing particle size.…”
Section: Introductionmentioning
confidence: 99%
“…In this study the findings of present study are in line with the findings of Lai et al (2005), where it was claimed that the reason of such a phenomenon is because of the effect of fewer intersections between the polymer and filler, while some researchers claim that the enhancement of the tensile strength during a reduction of flour size occurs because of the increase of contact surfaces (Nourbakhsh et al 2010). …”
Section: Tensile Strengthsupporting
confidence: 90%
“…However, the effect of nanographene on thermal stability depends on the type of polymer and processing conditions; nanographene in higher temperature ranges also increases the thermal stability (Nourbakhsh et al 2010). The most important effect of nanographene on the thermal stability is the formation of a non-burning coal-like layer.…”
Section: Effect Of Nanographene On Thermal Propertiesmentioning
confidence: 99%